Analysis Of Allocation Of Village Funds Through The Establishment Of Village Owned Enterprises (Bumdes) (Case Study On Bumdes Paya Tungel In Jagong Jeget District) - Nurjanah, Putria; Marliyah; Ahmad Hasibuan, Nur Fadhilah (Universitas Dehasen Bengkulu, 2023)
This study aims to analyze the allocation of village funds in supporting the development and empowerment of MSMEs through the establishment of BUMDes in Paya Tungel Village and identify the impact of allocating village funds through BUMDes on the development and empowerment of MSMEs in Paya Tungel Village. Paya Tungel Village, as a village in Central Aceh, has formed a Village-Owned Enterprise (BUMDes) in managing village funds with considerable potential for natural and human resources. BUMDes play an important role in improving the welfare of the local economy. By managing economic businesses based on local potential and resources, BUMDes create jobs, increase income, and reduce poverty rates in the village. By building a local-based economy, village communities become more economically independent. BUMDes can assist in developing local businesses, support farmers and small entrepreneurs, and take advantage of existing market opportunities to increase income and employment in the village. By focusing on local-based economic development, villages have a greater chance of achieving long-term economic sustainability. BUMDes can design programs that prioritize environmental protection and maintain a balance between economic growth and natural resource preservation.